An Analysis of Picture Books for Children Aged 3 to 6 Years: Portrayals of Engineers and the Engineering Design Process - Ata-Aktürk, Aysun; Demircan, H. Özlen (Springer Science and Business Media LLC, 2021)
The potential of children’s picture books to provide knowledge to support STEM education is high. Engineering is a field about which children may have little awareness or understanding. Children’s picture books can be an important tool in introducing engineering to children. In this study, we investigate children’s picture books written in or translated into Turkish for 3–6-years-old children to address two major points: (a) how engineers are portrayed and (b) how the engineering design process is included. We examined the content of 691 picture books and identified 23 books, in accordance with specific criteria (e.g., identification through predefined keywords), relevant to engineers and engineering. Findings indicated that characters who think and work like engineers were often portrayed as male characters rather than females. While 21 of the 23 books sampled discussed the engineering design process, none of these books identified all the steps in such a process. Children’s picture books are important tool to introduce engineering to children. We recommend the publication of more engineering-centered picture books to provide children with information about engineers and the engineering design process, in support of STEM education. However, it is important that such books do not allow misunderstandings to emerge about the field of engineering in the creation of characters or the messages conveyed.
Keywords: 4. Education